DAKWAH COMMUNICATION STRATEGY IN EMPOWERING THE LABOR COMMUNITY IN PANJANG DISTRICT BANDAR LAMPUNG CITY TO IMPROVE THEIR RELIGIOUS PRACTICE - Aliyandi Aliyandi (Akademika : Jurnal Pemikiran Islam, 2020)
This research is to explain about the role of Dakwah communication strategy in the empowerment of the labor community in Panjang Sub-District, Bandar Lampung in improving the practice of the implementation of sharia. This is descriptive qualitative research, where the data were collected throuh interviews, observation, and documentation. The data were then analyzed qualitatively using inductive thinking approach. The result of this research shows that the communication strategy used by the preacher in Panjang Sub-district was by giving motivation through the message of dawah conveyed to the community, Providing religious guidance, including religious activities such as five-time prayer, memorizing prayers, taking care of the corps and protecting the environment, establishing good relations with the community, either through regular recitation at the ta’lim assembly or taking the advantage of Arisan for savings and loan activities, interacting and seeing firsthand situation and conditions that exist in the community, then cooperate with the government by providing assistance in the form of funds and food. The most inhibiting factor is mad’u, especially in terms of understanding the message (somatic), closed to change (self-image), and motivation, marked by the passiveness communicant in receiving da’wah from the preacher because the preacher can not fully know the limits of somatic knowledge from the community.